Unleashing the Potential of CRISPR/Cas9 Genome Editing for Yield-Related Traits in Rice - Archana Thiruppathi; Shubham Rajaram Salunkhe; Shobica Priya Ramasamy; Rakshana Palaniswamy; Veera Ranjani Rajagopalan; Sakthi Ambothi Rathnasamy; Senthil Alagarswamy; Manonmani Swaminathan; Sudha Manickam; Raveendran Muthurajan (Plants)
Strategies to enhance rice productivity in response to global demand have been the paramount focus of breeders worldwide. Multiple factors, including agronomical traits such as plant architecture and grain formation and physiological traits such as photosynthetic efficiency and NUE (nitrogen use efficiency), as well as factors such as phytohormone perception and homeostasis and transcriptional regulation, indirectly influence rice grain yield. Advances in genetic analysis methodologies and functional genomics, numerous genes, QTLs (Quantitative Trait Loci), and SNPs (Single-Nucleotide Polymorphisms), linked to yield traits, have been identified and analyzed in rice. Genome editing allows for the targeted modification of identified genes to create novel mutations in rice, avoiding the unintended mutations often caused by random mutagenesis. Genome editing technologies, notably the CRISPR/Cas9 system, present a promising tool to generate precise and rapid modifications in the plant genome. Advancements in CRISPR have further enabled researchers to modify a larger number of genes with higher efficiency. This paper reviews recent research on genome editing of yield-related genes in rice, discusses available gene editing tools, and highlights their potential to expedite rice breeding programs.